Capture capability of different intrinsic structures for helium bubbles in micro-nano composite 304L steels. (September 2022) - Gao, Zhiying; Huang, Jia; Liu, Haocheng; Ge, Wei; Su, Yue; Luo, Fengping; Liu, Guoying; Shen, Tongde; Xue, Jianming; Wang, Yugang; Wang, Chenxu
Highlights: Micro-nano composite 304L stainless steel (MN304-La) is implanted with He + and annealed at 900 °C. Nano-precipitates, grain boundaries, and dislocation are three intrinsic structures coexisting in MN304-La. Three intrinsic structures have competing processes for capturing helium bubbles. Nano-precipitates exhibit the strongest strength in capturing helium bubbles compared to grain boundaries and dislocations. Abstract: The formation and migration of helium bubbles lead to performance degradation of structural materials in nuclear reactors. Intrinsic structures in nuclear materials can significantly influence the behavior and distribution of these helium bubbles under irradiation. Micro-nano composite 304L stainless steel (MN304-La) possesses three main kinds of intrinsic structures: grain boundaries (GBs), dislocations, and La-rich nano-precipitates (NPs). In this study, the helium bubbles on different intrinsic structures in MN304-La after He + ions implantation were characterized and analyzed. We compared the capabilities of different intrinsic structures in capturing helium bubbles and confirmed that NPs exhibit the strongest strength in capturing helium bubbles among the three kinds of intrinsic structures. We found that the competition of intrinsic structures for capturing helium bubbles depends on both the capture strength of the intrinsic structures and the capture distance to the helium bubbles.